A comparative electrophoretic study of some Ganoderma species collected from coconut trees (Cocos nucifera) and diseased oil palms (Elaesis guinensis). - Abdullah, Faridah; Lim, Tong Kwee; Mohamed, Rosli (1990)
During the mid-50's when oil palm replanting was extensive,symptoms of basal stem rot caused by Ganoderma were observed in large numbers on ageing palms. Today the pathogen is known to attack maturing palms as young as 5 years in age,resulting in considerable economic losses. High disease incidences were reported in fields which had previously supported coconuts and where the coconut palms were either left in situ after poisoning,or buried. The incidence was also high,although less consistent,in palms replanted in former oil palm stands. At the same time however, not all plantings on former oil palm or coconut stumps bore Ganoderma sporophores after 2 years felling. It has been implied that coconut stumps and especially trunks provide the infection faci for oil palm disease incidence. Pathogenicity tests to demonstrate that the same fungus on the coconut stumps were responsible for the oil palm disease has not been eztablished,mainly because pathogenicity tests involving Ganoderma has met very limited success. This investigation attempts to demonstrate the biochemical characters of Ganoderma collected from coconuts compared to those collected from diseased oil palms using horizontal polyacrylamide gel electrophoresis and analysing for several isozyme patterns of the Ganoderma from coconuts compared to those collected from diseases oil palms and several other diseased trees in England,U.K. The implication of this finding will be discussed.